Analysis of Cognitive Levels and Influencing Factors in Children with Obstructive Sleep Apnea - Jing Bi; Bo Yu; Guotong Zheng; Yangyan Yan; Yang Zhang; Xiaoyan Lin; Yiyuan Han; Chao Song (Children, 2024)
Background: Obstructive sleep apnea (OSA) in children is prevalent worldwide and affects their physiological, psychological, and cognitive functions. However, the research on OSA’s impact on children’s cognitive function remains inconclusive. This study aims to analyze the cognitive levels and influencing factors in children with OSA in a single-center study in China. Methods: We selected 110 children with OSA who visited the Department of Otorhinolaryngology, Head and Neck Surgery at the Children’s Hospital of Zhejiang University School of Medicine from March 2023 to April 2024. Cognitive function was assessed using the Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV), and data on the OAHI, BMI, lowest blood oxygen saturation, and tonsillar hypertrophy were collected. A correlation analysis was performed using SPSS Statistics 26.0. Results: The mean WISC-IV score of the children with OSA was 102.32, within the normal range. Gender and tonsillar grade had no significant effect on the cognitive levels. The BMI scores were significantly negatively correlated with verbal comprehension. The OAHI was weakly negatively correlated with perceptual reasoning but not with other cognitive dimensions. Conclusions: OSA may negatively affect specific cognitive domains in children, particularly perceptual reasoning and working memory. The BMI is a crucial factor influencing cognitive function in children with OSA. Future research should increase the sample size, include more variables, and conduct long-term follow-ups to comprehensively evaluate the influencing factors of OSA on children’s cognitive function.